A modified mathematical model of heat pump's condenser for analytical optimization. (1st February 2015) - Nyers, Jozsef; Garbai, Laszlo; Nyers, Arpad
Abstract: The aim of this article is to present the reason and the process of creating new modified mathematical model of heat pump plate condenser. The fundamental mathematical model is modified according to analytical optimization procedure. The adaptation is carried out by applying the procedure of elimination. The modified mathematical model include 2 governing equations instead of 6. The two governing equations contain 2 unknown dependent variables and 6 known parameters. The modified mathematical model is validated using the comparative method. The compared data are obtained by numerical simulation using fundamental and modified mathematical models. Applying both models the obtained data fully coincided. By using the new modified mathematical model and implementing the optimization process may lead to the determination of the maximum energy efficiency of hot water subsystem. The subsystem comprises a condenser, a circulation pump, a connecting pipeline and the heating units. The objective function in the optimization process is the coefficient of performance, COP, as a function of the mass flow rate of the hot water or of the circulation pump power. The paper offers the implementation of modeling the circulation pump power to achieve the maximum value of the COP. Highlights: A new modified mathematical model of heat pump's condenser was created. The modified and the fundamental model are steady-state with lumped parameters. The analytical optimization procedure required the modification. The fundamental model comprises 6 while modified 2 equations only. The deviations decrease with the increase of the circulation pump power.